Penggunaan Multimedia Interaktif Sebagai Metode Bercerita Guru Anak Usia Dini - Putri, Mayarista Rivana; Rahmawati, Ida Yeni; Rusdiani, Nurtina Irsad (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
The rapid development of technology is an urgency that drove this research to deeply examine the use of multimedia learning as a storytelling method for early childhood teachers. This descriptive qualitative research was conducted at TK Dharma Wanita 1 Demangan, involving the principal, three classroom teachers, and 27 students. Data collection was carried out through observation of the method's implementation and children's responses, interviews with the principal and teachers regarding the application and constraints, and documentation of the learning process. The results showed that the implementation of the multimedia-based storytelling method was well realized through four structured stages: planning, introduction, implementation, and evaluation. This method proved effective in enhancing four main aspects of child development, including learning attractiveness, language ability, creativity, cognitive development, and social development, characterized by the children's high enthusiasm and participation. The main supporting factors include the children's enthusiasm and the availability of technological devices, while the hindering factors involve infrastructure limitations and the lack of adequate teacher training. The contribution of this research is the affirmation that interactive multimedia is an effective and relevant medium for improving the quality of the storytelling method for Early Childhood Education (ECE) teachers.